Nitrogen and Phosphorus Co‐doped Hollow Carbon Spheres as Efficient Metal‐Free Electrocatalysts for the Oxygen Reduction Reaction. Issue 14 (7th March 2018) - Zhang, Chunmei; Hou, Lin; Cheng, Chunfeng; Zhuang, Zhihua; Zheng, Fuqin; Chen, Wei
Abstract: Replacement of rare‐ and noble‐metal catalysts with earth‐abundant, low‐cost, stable, and efficient metal‐free catalyst substitutes is highly desirable, but full of challenges for the oxygen reduction reaction (ORR). Herein, N, P co‐doped hollow carbon spheres (N, P‐HCS) are prepared through a simple pyrolysis method, using hollow carbon spheres (HCS), melamine, and phytic acid (PA) as the C, N, and P sources, respectively. Compared to the N‐doped HCS (N‐HCS) and P‐doped HCS (P‐HCS), the N, P co‐doped sample exhibited much higher ORR catalytic activity. Moreover, in comparison with commercial Pt/C, the as‐prepared N, P‐HCS showed comparable ORR activity, but stronger endurance to methanol and higher durability in alkaline solution. The high performance of N, P‐HCS can be primarily ascribed to the large surface area, high conductivity, porous carbon structure, and high content of heteroatoms (N and P). Considering the excellent catalytic activity and durability, after further structural optimization, N, P‐HCS could be a promising metal‐free catalyst candidate for the ORR in fuel cells. Abstract : Double dopping : N, P co‐doped hollow carbon spheres (N, P‐HCS) are prepared through a one‐step pyrolysis strategy using phytic acid (PA) and melamine as phosphorous and nitrogen precursors. Compared with commercial Pt/C, N, P‐HCS showed comparative current density, superior durability, and higher tolerance to methanol. The excellent oxygen reduction reaction (ORR) activity of N, P‐HCS indicates that the N, P co‐doping is an effective method to obtain highly active metal‐free catalysts for the ORR.